2015
DOI: 10.4066/amj.2015.2441
|View full text |Cite
|
Sign up to set email alerts
|

Cadazolid: A new hope in the treatment of Clostridium difficile infection

Abstract: Clostridium difficile infection (CDI) is a potential life-threatening consequence of antibiotic therapy. Although the risk increases with duration of treatment, it can also occur after a short treatment course. In addition to broad-spectrum antibiotics, anti-neoplastic agents, proton pump inhibitors, H(2) blockers, and several other drugs have been reported to induce intestinal dysbiosis, which is central to the pathogenesis of CDI. There is an increase in incidence and mortality attributed to CDI globally. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…The transposons are also involved in the resistance to chloramphenicol in C. difficile. Two mobile transposons, Tn4453a and Tn4453b, are able to transfer the catP gene, which encodes a chloramphenicol acetyltransferase enzyme that is responsible for the chloramphenicol resistance (25,41).…”
Section: Known Antimicrobial Resistance Mechanisms Of Clostridium Difmentioning
confidence: 99%
“…The transposons are also involved in the resistance to chloramphenicol in C. difficile. Two mobile transposons, Tn4453a and Tn4453b, are able to transfer the catP gene, which encodes a chloramphenicol acetyltransferase enzyme that is responsible for the chloramphenicol resistance (25,41).…”
Section: Known Antimicrobial Resistance Mechanisms Of Clostridium Difmentioning
confidence: 99%
“…CRS3123 is a favorable therapeutic agent that selectively inhibits the growth, spore and toxin production of C. difficile . The use of oral CRS3123 in hamsters resulted in a long lasting efficacy with essentially no recurrence, in significant contrast to existing CDI therapy with vancomycin [ 79 ]. CRS3123 has not demonstrated any cross-resistance to existing antibiotics and remains active against all tested C. difficile strains, more importantly the epidemic fluoroquinolone-resistant NAP1/BI/027 strain.…”
Section: Clinical Manifestations/diagnosis Of CDImentioning
confidence: 99%
“…Cadazolid, an oxazolidinone antibiotic, has demonstrated its potency in vitro against C. difficile , in addition to the epidemic BI/NAP1/027 strain [ 79 ]. A recent phase 2 multicenter, randomized, double-blinded study (NCT01222702; EUDRA-CT 2010-020941-29) assessed the efficacy and safety of oral cadazolid in treatment of CDI.…”
Section: Clinical Manifestations/diagnosis Of CDImentioning
confidence: 99%
“…The same is true for gut residing Enterococcus and Clostridia species. The former are associated with urinal infection in patients with catheter or catheter-related bloodstream infections and the latter is causing severe diarrhea by prolonged treatment with antibiotics or proton pump inhibitors [ 3 , 4 ]. In fact, a study involving 19 US hospitals during 2007 and 2010 revealed that the percentage of isolates of E. faecium being resistant to vancomycin was highest (87.1%) followed by S. aureus resistance to oxacillin–methicillin (56.8%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%